Eksistensi Perbankan Syariah di Tengah-Tengah Kebutuhan Perekonomian Modern - Nur, Nikmatullah (CV. Kalimasada Group, 2024)
The purpose of this study is to further review the existence of Islamic banking in the midst of modern economic needs. This research method adopts the style of writing literature articles. Literature articles are an approach that relies on written sources or literature as the main data to examine a topic or issue. In this method, researchers collect various relevant references, such as books, scientific journals, articles, research reports, laws and regulations, and other documents that can support the analysis. The conclusion obtained is that Islamic finance has developed rapidly as an important part of the global economy, especially in supporting the achievement of a more inclusive modern economy with an approach to the principles of social justice and sustainability. Islamic banking plays a core role in the financial sector which functions to collect funds and distribute them to the public in a fair and transparent way, making a positive contribution to the macro and micro economy. Along with the development of Islamic banking, the challenge of Islamic financial literacy in society must be overcome by collaboration between the government, financial authorities, and educational institutions, so that the financial sector can continue to make a significant contribution to the progress of the Indonesian and global economy.